2018
DOI: 10.1109/tvlsi.2018.2832051
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Channel 30-V Neural Stimulator for Spinal Cord Repair

Abstract: This paper presents a 15-channel, 30-V, implantable current stimulator for restoring locomotion control after spinal cord injuries. The stimulator features performance specifications comparable to those of large desktop instrumentation: high linearity, high precision of the delivered currents, small channel-to-channel mismatches and a fast settling time of 0.3 μs. An ADC-based active charge balancing scheme using a digital PI (proportional–integral) controller was implemented in firmware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The current of 1 mA is the industry standard for measurement of forward diode voltage and the 30 V reverse voltage was chosen with respect to the expected maximum voltage that will be present in implantable devices. A literature review in this area suggested that in most implantable devices, maximum voltage is limited to several volts and some stimulators use voltages up to 30 V to provide sufficient current when delivering neurostimulation pulses to high impedance tissue 34 36 . The dwell time between application of the voltage and measurement of 100 ms was chosen to measure the current under stable conditions, without presence of transient effects caused by linear lab power supply power-up.…”
Section: Methodsmentioning
confidence: 99%
“…The current of 1 mA is the industry standard for measurement of forward diode voltage and the 30 V reverse voltage was chosen with respect to the expected maximum voltage that will be present in implantable devices. A literature review in this area suggested that in most implantable devices, maximum voltage is limited to several volts and some stimulators use voltages up to 30 V to provide sufficient current when delivering neurostimulation pulses to high impedance tissue 34 36 . The dwell time between application of the voltage and measurement of 100 ms was chosen to measure the current under stable conditions, without presence of transient effects caused by linear lab power supply power-up.…”
Section: Methodsmentioning
confidence: 99%
“…These electronic devices have been proposed for treatment of neural disorders or dysfunction of the central and peripheral nervous system, 1–3 such as chronic pain, 4 Parkinson's disease, 5 epilepsy, 6,7 tremor, 8 dystonia, 9 tinnitus, 2 stroke, 10 bladder dysfunction, 11 obstructive sleep apnea, 12 and obesity 13 . ENSs have also been used to restore sensory and motor functions lost through injury or disease like implantable visual prosthesis, 14–16 cardiac pacemaker, 17 cochlear implant, 18–20 seizure control, 21,22 proprioceptive prosthesis, 23 bladder stimulators, 11 phrenic nerve stimulators, 24 vestibular prostheses, 25 and neuromuscular stimulation for restoring voluntary control of locomotion 26–31 . These prostheses establish a direct link between the neural stimulator and the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…13 ENSs have also been used to restore sensory and motor functions lost through injury or disease like implantable visual prosthesis, [14][15][16] cardiac pacemaker, 17 cochlear implant, [18][19][20] seizure control, 21,22 proprioceptive prosthesis, 23 bladder stimulators, 11 phrenic nerve stimulators, 24 vestibular prostheses, 25 and neuromuscular stimulation for restoring voluntary control of locomotion. [26][27][28][29][30][31] These prostheses establish a direct link between the neural stimulator and the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a high compliance voltage is required to deliver an applicable amount of charge to the tissue regardless of the amplitude of the stimulation current. Conventional current mode stimulator circuits exploit the high-voltage CMOS technology to achieve a high compliance voltage of the stimulator [2,3], which has significant disadvantages in power, area, and cost consumption.…”
mentioning
confidence: 99%
“…Since the injection of the stimulation current causes the accumulation of residual charge at the electrodeelectrolyte interface, creating a DC current flow that damages nerve tissue and corrodes the electrodes, the charge balancing function is required to mitigate the safety issue. While the active charge balancing (CB) scheme can remove the residual charge without an additional long discharging period, resulting in fast stimulation frequency, the passive CB scheme has advantages in terms of circuit complexity, power, and area consumption [2,3,4]. Given that the electrical stimulation for seizure suppression is effective in the low stimulation frequency of 5Hz [5], the passive CB scheme that minimizes the time constant associated with the resistance of the passive switches and the impedance of the electrode-tissue interface for reducing the discharge period can be a feasible alternative to the active CB scheme.…”
mentioning
confidence: 99%